The ancient farmstead at Lakkos (Kionia) on Tenos. An interdisciplinary study. (February 2023) - Angelopoulou, A.; Samaras, V.; Pantzouris, K.; Kravaritou, S.; Jakobitsch, T.
Highlights: The study is the first study of its kind conducted on the island of Tenos. The archaeological evidence shows olive oil production, viticulture and apiculture at the site Lakkos. It also highlights the significance of archaeobotanical research for the interpretation of excavation results. Archaeobotanical finds support the archaeological evidence for olive oil production. Specific soil conditions might have led to the preservation of a leaf of an olive tree. A study on the rooftiles of the agricultural building has been made. Abstract: This paper offers a preliminary presentation of the first, so far, known ancient farmstead on the island of Tenos in the Aegean Sea in Greece, confirming the significance of archaeobotanical research for the interpretation of archaeological data. At the site of Lakkos at Kionia, the building remains of an agricultural installation were discovered during a rescue excavation (2018–2019) conducted by the Ephorate of Antiquities of Cyclades of the Greek Ministry of Culture and Sports. The main period of use of the farmstead is dated in the Hellenistic and Roman eras (2nd century BCE-2nd century CE) covering a large span of time until its final abandonment during the 3rd and 4th centuries A.D. Both archaeological and archaeobotanical evidence confirm activities such as farming, oil, honey, and possibly wine production as well as processing and storage of goods at the site. Moreover, the discovery of an oil pressing installation elucidates aspects related to the oil extraction technology and the specialized agricultural industry in ancient Tenos. The study of Lakkos is expected to offer important new evidence regarding a series of understudied scientific issues related to the landscape, the agricultural economy, the rural habitation, the social organization, and the cultural significance of Tenos in antiquity.